2017
DOI: 10.1186/s13012-017-0561-4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying barriers to and facilitators of tuberculosis contact investigation in Kampala, Uganda: a behavioral approach

Abstract: BackgroundThe World Health Organization recommends routine household tuberculosis contact investigation in high-burden countries but adoption has been limited. We sought to identify barriers to and facilitators of TB contact investigation during its introduction in Kampala, Uganda.MethodsWe collected cross-sectional qualitative data through focus group discussions and interviews with stakeholders, addressing three core activities of contact investigation: arranging household screening visits through index TB p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
141
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(155 citation statements)
references
References 28 publications
(22 reference statements)
12
141
1
1
Order By: Relevance
“…Furthermore, ruling out TB in young children, especially in those <2 years old – the age group at highest risk of developing TB after exposure – involves recognition of warning signs and symptoms by parents and physicians, including the revision of growth charts These are not routinely recorded in TB contact investigation, hampering follow‐up. Training primary care staff on paediatric TB screening and diagnosis, strengthening communication between referral and primary care facilities, and designing forms to facilitate the appropriate recording and follow‐up of contacts may increase TB detection in and provision of preventive treatment to eligible contacts …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ruling out TB in young children, especially in those <2 years old – the age group at highest risk of developing TB after exposure – involves recognition of warning signs and symptoms by parents and physicians, including the revision of growth charts These are not routinely recorded in TB contact investigation, hampering follow‐up. Training primary care staff on paediatric TB screening and diagnosis, strengthening communication between referral and primary care facilities, and designing forms to facilitate the appropriate recording and follow‐up of contacts may increase TB detection in and provision of preventive treatment to eligible contacts …”
Section: Discussionmentioning
confidence: 99%
“…Previously, we identified several barriers to participants completing these steps, including a lack of knowledge about TB and its potential consequences; HIV and TB stigma; mistrust of health workers; and insufficient time and resources. [9,10] In 2013, the Uganda National TB and Leprosy Programme (NTLP) began implementing household TB contact investigation for all index TB patients in the country's capital, Kampala.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Vietnam reported that contacts and patients' knowledge, attitude, and practices regarding TB influenced continued engagement in the TB investigation process [14]. Another study from Uganda reported that stigma about TB, the constraint on time and space in clinics for counselling, mistrust of health-center staff by patients and contacts, and high travel costs for health staff to conduct contact screening and for contacts to travel to health facilities were barriers to implement TB contact screening [15].…”
Section: Discussionmentioning
confidence: 99%